Performance assessment of a Trigeneration plant driven by concentrated photovoltaic thermal system - Khammal Salim; Khouya Ahmed (EPJ Web of Conferences)
This study examines a Trigeneration system designed to provide cooling, heating and electricity for residential applications using a concentrated photovoltaic thermal system (CPVT). The CPVT system supplies the thermal energy for both cooling and electricity generation. The waste heat produced by the CPVT is utilized in buildings. The system operates with R124 as the fluid refrigerant. The results show that the proposed Trigeneration system reaches a maximum exergy efficiency of 12% and a thermal efficiency of 42%. Overall, the analyzed Trigeneration system demonstrates an efficient approach by integrating the concentrated photovoltaic thermal to produce cooling, heating and electricity for residential applications.